Triple metachronous primary cancer of uterus, colon, and breast cancer: A case report and review of the literature - Li, Guanqiao (Medicine (Baltimore), 2020)
RATIONALE: Triple or more primary malignancies are rare, with only 23 previous cases including breast cancer reported in the English language studies between January 1990 and December 2019. PATIENT CONCERNS: The patient was a 67-year-old woman with a mass in her right breast. She had a previous history of uterine and colon cancer. Both ultrasonography and mammography revealed a Breast Imaging Reporting and Data System (BI-RADS) category 3 breast lesion, in which proliferative nodules are more likely. Given her previous history of 2 malignancies, her doctors strongly recommended a biopsy. DIAGNOSIS AND INTERVENTIONS: The biopsy pathology suggested intraductal breast cancer. Mastectomy and sentinel lymph node biopsy were performed. The postoperative pathological diagnosis was invasive ductal carcinoma, grade II, stage I. The sample was positive for estrogen receptor and progesterone receptor and negative for cerbB-2. No radiotherapy or chemotherapy was administered except for endocrine therapy. A follow-up at 19 months showed no breast recurrence or distant metastases. OUTCOMES: No recurrence or distant metastasis occurred within the 19-month, 11-year, and 20-year follow-ups for breast, colon, and uterine cancers, respectively. LESSONS: To our knowledge, this is the first review of triple or more primary malignancies including breast cancer. These malignancies occur predominantly in older female patients. The most prevalent tumors of triple or more primary malignancies including breast cancer occur in the colon, uterus, and lung. A favorable prognosis is associated with early-stage malignancies.